Response of soil carbon dioxide efflux to temporal repackaging of rainfall into fewer, larger events in a semiarid grassland - Roby, Matthew C.; Scott, Russell L.; Biederman, Joel A.; Smith, William K.; Moore, David J. P. (Frontiers in Environmental Science, 2022)
Changing rainfall patterns will alter soil water availability to plants and microbes and likely impact soil CO2 efflux (Fs) in semiarid ecosystems. However, our understanding of the response of Fs to compound changes in rainfall event size and frequency remains relatively limited. To address this knowledge gap, we examined how compound changes in rainfall size and frequency impact Fs in a semiarid grassland by deploying automated soil chambers at a rainfall manipulation experiment. All plots within the experiment received equal total summer growing season precipitation that was temporally repackaged into regular events of inversely varied size and frequency, with event sizes ranging from 5-50 mm and dry intervals ranging from 3.5-21 days. We found that repackaging rainfall into few/large events with long dry intervals decreased seasonal cumulative Fs. Repackaging influenced key aspects of pulses including mean, maximum, and antecedent (day before irrigation) values of soil moisture and Fs and their rate of decline during drying intervals. Soil moisture explained substantial variation in Fs (R2 > 0.84) for all treatments; however, the sensitivity of Fs to soil moisture decreased in the few/large regime compared to the reference and many/small regimes. Dynamics in plant phenology (quantified by plot greenness) and soil temperature interacted with soil moisture to influence the seasonal evolution of Fs pulses and cumulative efflux. Our findings demonstrate that soil moisture and vegetation responses to changes in rainfall size and frequency impact soil CO2 efflux pulses and seasonal emissions in semiarid grasslands. These results, coupled with the knowledge that CO2 efflux pulses play an outsized role in dryland carbon exchange, indicate the possibility of future climate-mediated shifts in the carbon cycling of semiarid ecosystems.